The coupled thermal-structural response of RC beams during fire events based on nonlinear numerical simulation. (January 2020) - Elshorbagy, Mohamed; Abdel-Mooty, Mohamed
Highlights: A validation of numerical simulation of RC-beams during fire events using ANSYS against experimental work. Effect of lateral support stiffness on the structural response of RC-beams during fire. Concrete cover significant effect on both thermal and structural response of the RC-beam during fire. The effect of concrete compressive strength of RC-beams during fire. Abstract: In this paper and based on a previous work, a parametric study was executed to capture the crucial parameters that affect the response of reinforced concrete beams, whether the thermal response or the structural response. The aim behind the used methodology from the previous work was reaching a reliable algorithm that has the capability to simulate any reinforced concrete element under both mechanical and fire loads. This algorithm is based on connecting thermal analysis and structural analysis with coupling technique called sequential coupling technique. This technique allow taking into consideration the non-linearity for thermal material properties such as conductivity, specific heat, and density, and also the non-linearity for mechanical properties such as stress-strain relationship, and thermal expansion coefficient, beside the nonlinearity for concrete compressive strength, and rebar ultimate strength. This algorithm is achieved through detailed numerical finite element models using ANSYS program. The main parameters that had been studied in this paper are the effect of increasing concrete compressive strength, increasing concrete cover, and the effect of increasing the lateral stiffness of the beam on the total response.